Cooperation and conflict in intra‐hospital transfers: A qualitative analysis - Hayley D. Germack; Renee Fekieta; Meredith Campbell Britton; Shelli L. Feder; Alana Rosenberg; Sarwat I. Chaudhry (Wiley, 2020)
Abstract Aim The purpose of this study was to explore the latent conditions of cooperation and conflict in intra‐hospital patient transfers (i.e. transfers of patients between units in a hospital). Design Secondary qualitative analysis of 28 interviews conducted with 29 hospital staff, including physicians (N = 13), nurses (N = 10) and support staff (N = 6) from a single, large academic tertiary hospital in the Northeastern United States. Methods A two‐member multidisciplinary team applied a directed content analysis approach to data collected from semi‐structured interviews. Results Three recurrent themes were generated: (a) patient flow policies created imbalances of power; (b) relationships were helpful to facilitate safe transfers; and (c) method of admission order communication was a source of disagreement. Hospital quality improvement efforts could benefit from a teaming approach to minimize unintentional power imbalances and optimize communicative relationships between units.